Role of health locus of control in preventing occupational decompression sickness among deep-sea fisherman divers - Chanon Kongkamol; Piyada Kongkamol; Chutima Phanlamai; Pornchai Sathirapanya; Chutarat Sathirapanya (Health Psychology and Behavioral Medicine, 2023)
ABSTRACTBackground Indigenous fisherman divers frequently experience decompression sickness (DCS). This study aimed to evaluate the associations between the level of knowledge of safe diving, beliefs in the health locus of control (HLC), and regular diving practices with DCS among the indigenous fisherman divers on Lipe island. The correlations among the level of beliefs in HLC, knowledge of safe diving and regular diving practices were evaluated also.Method We enrolled the fisherman divers on Lipe island and collected their demographics, health indices, levels of knowledge of safe diving, beliefs in external and internal HLC (EHLC and IHLC), and regular diving practices to evaluate the associations with the occurrence of DCS by logistic regression analysis. Pearson’s correlation was used to test the correlations among the level of beliefs in IHLC and EHLC, knowledge of safe diving, and regular diving practices.Results Fifty-eight male fisherman divers whose mean age was 40.39 (±10.61) (range 21–57) years were enrolled. Twenty-six (44.8%) participants had experienced DCS. Body mass index (BMI), alcohol consumption, diving depth, duration of time in the sea/dive, level of beliefs in HLC and regular diving practices were significantly associated with DCS (p < 0.05). Level of belief in IHLC had a significantly strong reverse correlation with that in EHLC and a moderate correlation with level of knowledge of safe diving and regular diving practices. By contrast, level of belief in EHLC had a significantly moderate reverse correlation with level of knowledge of safe diving and regular diving practices (p < 0.001).Conclusions Encouraging the fisherman divers’ belief in IHLC could be beneficial for their occupational safety.